Are there asymmetries in the effects of training on the conditional male wage distribution? - Wiji Arulampalam; Alison L. Booth; Mark L. Bryan (Institute for the Study of Labor (IZA), 2004)
We use a quantile regression framework to investigate the degree to which work-related training affects the location, scale and shape of the conditional wage distribution. Human capital theory suggests that the percentage returns to training investments will be the same across the conditional wage distribution. Other theories – whether based on imperfections in the labour market or on skill-mix heterogeneity – suggest that this need not be the case. Using the first six waves of the European Community Household Panel, we investigate these issues for private sector men in ten European Union countries. Our results show that, for the vast majority of countries, investment in training yields similar percentage returns across the conditional wage distribution. Only Belgium was an outlier in this respect. However, our results do indicate that there are considerable differences in mean returns to training across countries.
Keywords: C29; J31; J24; 330; private sector training; wages; education; quantile regression; Weiterbildung; Bildungsinvestition; Bildungsertrag; Lohnstruktur; Schätzung; EU-Staaten